"I don't have much of a choice": Low‐income single mothers' COVID‐19 school and care decisions. Issue 5 (21st September 2021) - Radey, Melissa; Langenderfer‐Magruder, Lisa; Brown Speights, Joedrecka
Abstract: Objective: This study used a preferences and constraints framework to understand mothers' decision‐making processes around childcare and schooling during the COVID‐19 pandemic and how socioeconomic context contribute to these decisions. Background: Despite potential long‐standing consequences of school decision making during the COVID‐19 pandemic, we know little about how parents consider childcare and education options during these times. And, these decisions are particularly important for single mothers in resource‐scarce environments whose children benefit disproportionately from appropriate care and education. Method: This study used qualitative data gathered from semistructured interviews with low‐income, single mothers ( N = 34). Results: Approximately half of mothers selected home‐based care while the other half selected site‐based care. Findings suggest that mothers made decisions largely on the basis of constraints—safety or financial need. Given high levels of fear and system mistrust, Black mothers more commonly selected home‐based care than White mothers. Conclusion: The COVID‐19 pandemic seems to exacerbate the restricted childcare calculus of low‐income mothers. Implications: Partnering with communities and disseminating accurate information, particularly in Black communities, is critical for establishing trust and positioning low‐income single mothers to make current care and education decisions, as well as future decisions, such as vaccination decisions.